Seven Criteria for the Assessment of the Ecclesial Identity and Vocation of a Particular Church: The Development of an Interpretative System Based on the Ecclesiology of Vatican II and Verified Against the Work of the Kyivan Church Study Group - Sakvuk, Yuriy (Université Saint-Paul / Saint Paul University, 2011)
The dissertation aims to do three things: First, it provides a survey of the historical and theological background of the Council; the Council’s principal tasks and major ecclesiological documents concerned with the ecclesial identity and vocation of a Particular Church; and the general reshaping of Catholic ecclesiology in the light of documents of the Council. Second, using pertinent documents of the Council and the reflections of Catholic theologians, it presents an original interpretative system for evaluating the ecclesial identity and vocation of any given Particular Church of the Catholic communion Eastern or Western) through the use of seven interdependent criteria. These are 1. A return to the authentic traditional roots of a particular tradition and the need for proper and organic reform within a given Particular Church; 2. Restoration and development of a particular theology; 3. Restoration and development of particular ways of liturgical worship; 4. Restoration and development of particular ecclesiastical legislation; 5. Restoration and development of a particular spiritual patrimony; 6. Preservation of and contribution to the already existing communion of the Particular Churches; 7. Work towards inter-confessional rapprochement, inter-religious dialogue and universal integration. Third, it will demonstrate how the interpretative system composed of seven criteria delineated from the documents of Vatican II can be verified by its practical application to the assessment of the concrete vision of the ecclesial identity and vocation of the Kyivan Catholic Church as it was presented and explained by the Kyivan Catholic and Orthodox members of the ecumenical body known as the Kyivan Church Study Group.
Keywords: Particular Church; Ecclesia Particularis; Ritus; Rite; Ecclesia localis; Ecclesia Sui Iuris; Autonomous Church; Self-Governing Church; Local Church; Ecclesial Identity; Kyivan Church; Kyivan Church Study Group; Ukrainian Catholic Church; Ukrainian Greek-Catholic Church; Ukrainian Greco-Catholic Church; Vatican II; Second Vatican Council; Unitatis Redintegratio; Lumen Gentium; Orientalium Ecclesiarum; Eastern Catholic Churches; Catholic Communion; criteria of ecclesial particularity